Developing math games media using scratch language. (October 2020) - Bernard, M; Setiawan, W
Abstract: Problems faced by students on mathematical problems always occur due to process errors because for those with enough knowledge to memorize formulas, then their job is only to insert numbers in formulas, and in fact, even when they use them they are not able to develop reasonable process stages. The purpose of this media learning, the existence of a strong positive influence they can understand mathematics, able to tune in concepts and be able to evaluate if there are steps in the wrong process then they correct mistakes. This study aims to develop the potential of prospective teachers or students to create ICT-based interactive media in mathematical games, using the ADDIE model of Analysis, Design, Development, Implementation, and Evaluation to see and guide students in making better products. From the results of the study that there is a positive influence when using media based on the average class at pretest 70.74 and post-test 82.69 with paired t-test with a significant value of 0, 000 <0.05. and there is also an increase in the ability to solve the context of mathematical problems using the scratch program language based on a decrease in the indicators of student difficulties.